PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS DISCOVERY LEARNING PADA MATERI VEKTOR PESERTA DIDIK KELAS X SMA KPG KHAS “PAPUA” MERAUKE - ROSALINA ESTI LESTARI; VIRMAN VIRMAN (Jurnal Ilmu Pendidikan Indonesia, 2018)
This research is a research and development (Research & Development) which aims to find out how to develop physics learning module based on discovery learning on vector material of class X students of SMA KPG Typical "Papua" Merauke. Number of samples of study 21 students of class X MIA-2 SMA KPG Typical "Papua" Merauke. Data analysis techniques used descriptive presentative to determine the feasibility of the module. The results showed that: (1). Module development module starts from potential problem analysis, module planning, module drafting, and development; (2). The feasibility of module from media validator was obtained percentage of average result of 81.96% with very feasible category, material validator equal to 95.62% with very decent category, and result of student response equal to 87.29% with very good category; (3). Excess module that was module contextually according to local wisdom of Papua especially Merauke and improved learners learn result with result of average of n-Gain test equal to 0.64 with medium concept concept category; (4). The shortcomings of the module were the less developed discovery learning stage in the module more broadly.  Keywords: Discovery Learning, Learning Outcomes, and Physics Module.